POTASSIUM PERMANGANATE AS OXIDANT IN THE COD TEST FOR SALINE WATER SAMPLES - Chin-Ping Goh; Poh-Eng Lim (ASEAN Journal on Science and Technology for Development, 2008)
The objective of this study is to investigate the feasibility of applying potassium permanganate (KMnO4) as the oxidant in the COD test for highly saline water samples. Initially, the COD values of various glucose standard solutions were determined by three methods, namely the standard closed reflux dichromate (CODCr), the acidic permanganate (CODMn) and the alkaline permanganate (CODOH) methods. The results showed that at COD values lower than 20 mg/L, the standard dichromate method was not applicable due to its poor precision (RSD > 10%). The CODOH method was less effective compared to the CODMn  method as the recoveries were 0.71 and 0.89, respectively. The determination of CODOH for the standard solutions of glucose in the presence of Cl- and Br-, respectively, or both Cl-  and Br-  ions were conducted. The results showed that the COD values only increased 5.1% with the increase in chloride concentrations up to 35000 mg Cl-/L. This shows that the CODOHmethod is a suitable method for determining the COD of highly saline water samples such as estuarine and coastal waters. The COD test was conducted for river, estuarine and coastal water samples. The results indicated that the CODOH test correlates well with the CODCr test (R2  > 0.98). The results also indicated that this CODOH test can be applied in determining the pollution trends for estuarine and coastal waters.